New Evaluation Technique for WTG Design Wind Speed Using a CFD-Model-Based Unsteady Flow Simulation with Wind Direction Changes - Takanori Uchida; Takashi Maruyama; Yuji Ohya (Modelling and Simulation in Engineering)
Because a significant portion of the topography in Japan is characterized by steep, complex terrain, which results in a complex spatial distribution of wind speed, great care is necessary for selecting a site for the construction of wind turbine generators (WTG). We have developed a CFD model for unsteady flow called RIAM-COMPACT (Research Institute for Applied Mechanics, Kyushu University, computational prediction of airflow over complex terrain). The RIAM-COMPACT CFD model is based on large eddy simulation (LES). The computational domain of RIAM-COMPACT can extend from several meters to several kilometers, and RIAM-COMPACT can predict airflow and gas diffusion over complex terrain with high accuracy. The present paper proposes a technique for evaluating the deployment location of a WTG. The proposed technique employs the RIAM-COMPACT CFD model and simulates a continuous wind direction change over 360 degrees.